Anti-blast performance of 3D-printed sandwich panels with auxetic hexagonal and regular hexagonal honeycomb cores. (1st December 2022) - Yan, Zichen; Liu, Yan; Yan, Junbo; Wang, Baichuan; Bai, Fan; Shi, Zhenqing; Huang, Fenglei
Highlights: Blast experiments were conducted to study the close-in blast effect and failure characteristics of honeycomb HSPs. The blast performance of auxetic HSPs is compared with regular hexagonal HSPs. Simulation is in good agreement with experiments and can describe the deformation and fracture damage. The effect of the core type and unit-cell angle on the damage of HSPs is investigated. Abstract: 3D-printed auxetic honeycomb sandwich panels (HSPs) have considerable potential for blast resistance enhancement. This study aims to bridge the gap with regard to the experimental data on the effect of 3D-printed auxetic hexagonal honeycomb cores on the blast response of HSPs. To this end, the blast resistance of HSPs developed using auxetic re-entrant and regular hexagonal honeycomb cores is investigated experimentally and numerically. First, six HSPs are tested under close-in blast loadings. The HSPs comprise Q345 steel top and bottom sheets as well as a honeycomb aluminum alloy core with two configurations (regular hexagonal and auxetic re-entrant). According to the results, the former configuration enhances the HSP blast resistance by not only decreasing the deformation of the HSPs but also improving their damage tolerance. In addition, the responses of the HSPs are numerically studied via finite element analysis. The numerical method using the finite element program LS-DYNA achieves reasonable accuracy. Finally, a parametric study is conducted to investigate the effects of the honeycomb type, cell angle, debonding effects, and core material on the blast resistance of the HSPs. The results demonstrate that employing auxetic hexagonal honeycomb core, smaller cell angle, and ductile core material can improve the blast resistance of HSPs.